A method for granulating phosphate tailings and phosphate tailings particles prepared therefrom and applications thereof
By using composite binders of tannin acid, lignin sulfonate and tea saponin, the problem of difficulty in pelleting phosphorus tailings is solved, and phosphorus tailings particles with high particle formation rate, particle strength and dispersion are prepared, achieving efficient utilization of resources and environmental sustainability.
Patent Information
- Application Number
- CN202411013654.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-26
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-07-26
AI Technical Summary
As a sandy material, phosphorus tailings are difficult to granulate and have poor granulation effect, resulting in low utilization rate, storage and occupancy of land, and environmental threats.
Tannic acid, lignin sulfonate and tea saponin are used as composite binders to achieve granules of phosphorus tailings through complexing reaction and increasing fluidity and surfactivity.
The prepared phosphorus tailings particles have excellent granulation rate, particle strength and dispersion, meet the national standards for calcium, magnesium, phosphorus fertilizer, and have simple process and low cost, and have broad industrialization potential.
Smart Images

Figure CN118930373B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of waste resource recovery and safe utilization, and more specifically to a method for granulating phosphorus tailings, phosphorus tailings particles prepared therefrom, and applications thereof. Background Art
[0002] With the continuous expansion of the scale of the phosphorus chemical industry, the accumulation of phosphorus tailings has continued to increase, but the utilization rate is only 20%. The storage of phosphorus tailings occupies a large amount of land and poses a huge potential threat to the environment. Phosphate tailings are rich in calcium and magnesium nutrients and have a certain alkalinity, which has the potential to prepare soil conditioners and medium-element fertilizers. Phosphate tailings are usually in powder form. Although powders can produce better fertilizer effects in agricultural applications due to easier release of nutrients, they are not suitable for the requirements of agricultural mechanization. In addition, if the granulated granular products cannot disintegrate in the soil, it will affect the fertilizer effect. Therefore, granulating the raw materials and ensuring high granule strength and rapid disintegration rate are the problems that the industry urgently needs to solve.
[0003] However, as a typical sandy material, phosphorus tailings are difficult to granulate like calcium magnesium phosphate fertilizer, potassium chloride, ammonium chloride and other sandy materials. Taking phosphorus tailings as an example, its main components are dolomite CaMg (CO 3 ) 2 , the larger charge between calcium and magnesium ions and carbonate particles means that the electrostatic attraction between positive and negative ions is stronger, resulting in higher ionic bond energy. And because of its hexagonal crystal structure, the ions are closely arranged in the lattice, and the overall strength of the ionic bonds is large, resulting in insufficient hydration energy to overcome its strong lattice energy, further making the material insoluble in water and difficult to form liquid bridges during the granulation process. In addition, due to the low surface activity of phosphate tailings, the mutual attraction of particles is weakened during the granulation process, making it difficult for the particles to bond naturally. In short, due to the influence of its own tight ionic structure and low viscosity, a series of sandy materials such as phosphate tailings are difficult to granulate and the granulation effect is poor.
[0004] Chinese invention patent CN109796278B has developed a method for preparing a binder suitable for low-concentration compound fertilizers. The fertilizer binder is prepared by using lignin, gypsum and polyacrylamide in different proportions. The final product has the characteristics of high granulation rate and strong particle compression. However, its application scenarios are mainly raw materials such as urea with high viscosity. Whether it can be used in low-viscosity or even non-viscosity sandy materials, and whether it can achieve rapid disintegration of the product in the soil while having high particle strength, are not clear.
[0005] Chinese invention patent CN108503464A provides a granular medium-trace element fertilizer and a production method thereof, which mainly uses raw materials such as polyacrylamide, polyvinyl alcohol, lignin, etc. as binders to achieve efficient granulation of sandy materials such as yellow phosphorus slag. Although it has high particle strength and fast disintegration rate at the same time, the binders used are mostly artificial synthetic polymers, which not only cause high production costs, but also these materials will produce microplastic pollution when applied to the soil with the fertilizer.
[0006] In summary, there is an urgent need for a low-cost, high-efficiency, and natural non-polluting binder to achieve granulation of sandy materials. Summary of the invention
[0007] In view of the above problems, the present invention provides a method for granulating phosphate tailings and phosphate tailings particles prepared therefrom and applications thereof. Tannic acid, lignin sulfonate and tea saponin are used as composite binders for granulating phosphate tailings. The prepared phosphate tailings particles have excellent granulation rate, particle strength and solubility.
[0008] A first object of the present invention is to provide a method for granulating phosphate tailings, comprising the following steps:
[0009] The composite adhesive is obtained by uniformly mixing tannic acid, lignin sulfonate and tea saponin;
[0010] The composite binder is evenly mixed with the phosphate tailings powder and then granulated. Tannic acid and lignin sulfonate undergo a complex reaction, and tea saponin increases fluidity and surface activity, so that the composite binder penetrates into the phosphate tailings powder to play a bonding role, thereby preparing phosphate tailings particles.
[0011] In a preferred embodiment of the present invention, the mass ratio of tannic acid, lignin sulfonate and tea saponin is 2.5-3:30-70:30-70. For example, the mass ratio of tannic acid, lignin sulfonate and tea saponin is 2.5:30:70, 2.5:40:60, 2.5:50:50, 2.5:60:40, 2.5:70:30, 2.8:30:70, 2.8:50:50, 2.8:70:30, 3:30:70, 3:50:50 or 3:70:30, but is not limited to the listed values. Other values not listed within the above numerical range are also applicable.
[0012] In a preferred embodiment of the present invention, the mass ratio of tannic acid, lignin sulfonate and tea saponin is 2.5:30-70:30-70.
[0013] In a preferred embodiment of the present invention, the mass ratio of tannic acid, lignin sulfonate and tea saponin is 2.5:50:50.
[0014] In a preferred embodiment of the present invention, the amount of the composite binder added is 1% to 2% of the mass of the phosphate tailings powder. For example, the amount of the composite binder added is 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2% of the mass of the phosphate tailings powder, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0015] In a preferred embodiment of the present invention, the lignin sulfonate is sodium lignin sulfonate or calcium lignin sulfonate.
[0016] In a preferred embodiment of the present invention, the effective phosphorus content of the phosphate tailings is 0.5% to 1%, the effective magnesium content is 4% to 7%, and the effective calcium content is 8% to 14%.
[0017] The second object of the present invention is to provide phosphate tailings particles obtained by the above granulation method.
[0018] The third object of the present invention is to provide the application of the above-mentioned phosphate tailing particles in soil improvement.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) The present invention is inspired by natural mussels, combines lignin sulfonate with tannic acid, and the complexation reaction of lignin and tannic acid simulates the self-condensation of mussel adhesive protein to achieve the preparation of a pure natural high-performance adhesive. On this basis, tea saponin is innovatively added as an adhesive dressing to increase the fluidity and surface activity of the lignin and tannic acid adhesive, making it easier to penetrate into the interior of the phosphate tailings to play an adhesive role. All materials come from nature and are biodegradable and pollution-free.
[0021] (2) The present invention provides a granulation method and application of phosphate tailings, which provides an effective disposal measure for the large-scale accumulation of phosphate tailings, an industrial by-product.
[0022] (3) The phosphate tailing particles prepared by the present invention have good physical properties, can meet the national standards for calcium magnesium phosphate fertilizer, and have a simple preparation process, low cost, and broad industrialization potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Scanning images of phosphate tailings particles, wherein a is a surface scanning image of Comparative Example 2 at a scale of 100 μm, b is a cross-sectional scanning image of Comparative Example 2 at a scale of 100 μm, and c is a cross-sectional scanning image of Comparative Example 2 at a scale of 100 μm; d is a surface scanning image of Example 3 at a scale of 100 μm, e is a cross-sectional scanning image of Example 3 at a scale of 100 μm, and f is a cross-sectional scanning image of Example 3 at a scale of 10 μm. DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] As described in the background art, there is a need for a low-cost, high-efficiency, and natural non-polluting binder to achieve granulation of sandy materials.
[0026] Some marine organisms in nature can secrete adhesive proteins to firmly adhere to various substrate surfaces underwater. In particular, mussels rely on foot threads and the mussel adhesive proteins they secrete to tightly adhere their bodies to the wet and hard reef surfaces. Studies have shown that mussel adhesive proteins have super strong adhesion properties and adaptability in various environments. Its function is mainly because mussel adhesive proteins are rich in l-3,4-dihydroxyphenylalanine (DOPA) amino acids, in which catechol molecules can form various non-covalent and covalent interactions, which contribute to interfacial adhesion and cohesion. In depth, the cohesion (such as through cation-π interactions) and adhesion (such as the water absorption of amines helps catechols to hydrogen bond with wet surfaces) are enhanced through the synergistic effect of DOPA-lysine (catecholamines). The inventors use these inspirations from nature to produce natural and efficient adhesives and apply them in industry.
[0027] The specific technical solutions are as follows:
[0028] A method for granulating phosphate tailings comprises the following steps:
[0029] The composite adhesive is obtained by uniformly mixing tannic acid, lignin sulfonate and tea saponin;
[0030] The composite binder and the phosphate tailings powder are uniformly mixed and then granulated to obtain phosphate tailings particles.
[0031] The present invention uses lignin sulfonate as the main carrier of the binder. Lignin sulfonate is a byproduct of the papermaking industry, has the characteristics of rich sources and non-toxicity, and the loaded sulfonate has good water solubility, and also has certain swelling and surface activity. Further, the present invention uses tannic acid as a modifier to prepare a lignin-tannic acid composite binder. Tannic acid is a natural high molecular weight water-soluble polyphenol compound that can be extracted from a variety of plants such as Chinese gallnut, pomegranate, and witch hazel. It is composed of five pyrogallol groups and five catechol end groups, and has a structure and function similar to that of catechol molecules in mussel adhesive proteins. Tannic acid can be combined with polysaccharides through hydrophobic bonds and multi-point hydrogen bonds as a skeleton, and through the complexation reaction of lignin and tannic acid, the self-condensation of mussel adhesive proteins is simulated to achieve the preparation of a pure natural high-performance binder.
[0032] The present invention innovatively adds tea saponin as a binder auxiliary material on the basis of the above. Tea saponin is a saponin, also known as saponin, saponin or saponin. It is a mixture of a class of oleanane-type pentacyclic triterpenoid saponins. The basic structure consists of three parts: sapogenin, glycoside and organic acid, and has strong surface activity. After the steady-state treatment of tea saponin, the fluidity and surface activity of the lignin-tannic acid adhesive are increased, and it is easier to penetrate into the interior of the phosphate tailings to play an adhesive role, so that the finally formed lignin-tannic acid-tea saponin composite adhesive has the characteristics of strong bonding force, good dissolution and fast curing speed, and further improves the granulation rate, particle strength and dissolution of the product particles. And tea saponin is in solid form, which is convenient for addition during the granulation process.
[0033] All raw materials of the present invention are lignin, tea saponin and tannic acid which can be extracted from nature, which are biodegradable and environment-friendly materials, and have low production cost and simple process. The strength and solubility of product particles can be significantly improved, thus achieving multiple optimization of economic benefit, environmental effect and product effect.
[0034] Furthermore, the mass ratio of tannic acid, lignin sulfonate and tea saponin is 2.5-3:30-70:30-70.
[0035] In the preparation process, if the mass ratio of tannic acid to tea saponin is too low, the granulation effect of phosphorus tailings will be poor, and if the mass ratio is too high, the cost will be too high. The present invention uses tannic acid and tea saponin as two raw materials to optimize the effect of lignin as a raw material on the granulation of phosphorus tailings.
[0036] The added amount of the composite binder is 1% to 2% of the mass of the phosphate tailings powder.
[0037] During the preparation process, the composite binder needs to be weighed according to the above-mentioned mass percentage. If it exceeds the above parameter range, the addition amount of the composite binder is too low, which is not conducive to achieving the desired effect of the product. If the addition amount of the composite binder is too high, it will increase the cost on the one hand, and on the other hand, it may cause excessive viscosity and reduce the granulation rate of the final product.
[0038] Furthermore, the lignin sulfonate is sodium lignin sulfonate or calcium lignin sulfonate.
[0039] Furthermore, the granulated product is sieved through a 2 mm to 4 mm sieve and then dried at 60° C. to 90° C. for 3 h to 6 h to obtain phosphorus tailings particles.
[0040] In principle, the present invention has no particular restrictions on the drying and particle size of the phosphate tailings powder. Those skilled in the art can select and adjust according to actual application conditions, product requirements and quality requirements. In order to better improve the reaction between components, the present invention further obtains the phosphate tailings powder by drying the phosphate tailings and crushing them through a 40-80 mesh sieve.
[0041] Furthermore, phosphate tailings are by-products of the production of phosphate fertilizers in the phosphate chemical industry, with an effective phosphorus content of 0.5% to 1%, an effective magnesium content of 4% to 7%, and an effective calcium content of 8% to 14%.
[0042] According to the granulation method of the present invention, a phosphate tailings particle is prepared, which can be used as an acidic soil conditioner or a medium and trace element fertilizer. The phosphate tailings particle provided by the present invention can improve the soil pH and supplement the calcium and magnesium elements in the soil, has an improvement effect on the acidic red soil lacking calcium and magnesium, and is easier to transport and spread than powdered fertilizers.
[0043] All raw materials of the present invention are not particularly limited in their sources, and can be purchased on the market or prepared according to conventional methods well known to those skilled in the art. The phosphate tailings used in the present invention are purchased from Yunnan Phosphate Chemical Group, tannic acid is purchased from Beekman Biological Company, sodium lignin sulfonate is purchased from Yuanye Biological Company, and tea saponin is purchased from Yuanye Biological Company.
[0044] In order to further illustrate the present invention, a method for granulating a phosphate tailings provided by the present invention is described in detail below in conjunction with examples. However, it should be understood that these examples are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operating procedures are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention, and the protection scope of the present invention is not limited to the following examples.
[0045] Example 1
[0046] This embodiment provides a method for granulating phosphate tailings with a mussel-like structure, comprising the following steps:
[0047] Step 1, drying the phosphate tailings in an oven at 60° C. for 3 h, then crushing and passing through an 80-mesh sieve to obtain phosphate tailings powder;
[0048] Step 2, 2.5 g of tannic acid powder, 70 g of sodium lignin sulfonate powder, and 30 g of tea saponin powder are passed through an 80-mesh sieve and mixed evenly to obtain a composite adhesive;
[0049] Step 3, first put 50wt% of phosphorus tailings powder into the granulation disk, weigh the composite binder powder according to 2% of the total phosphorus tailings powder mass, evenly sprinkle 50wt% of the composite binder on the raw material mixture, and continuously clean the raw materials bonded on the disk wall with a brush to gather them in one place. At the same time, spray water in small quantities and multiple times in the disk to wet the surface of the composite raw materials and provide dissolution and reaction conditions for the binder. When the powder absorbs moisture exceeding the maximum molecular combined moisture under the action of the binder, capillary water will be formed, which can migrate faster and pull the particles around the water droplets to the center of the water droplets, combine the high viscosity provided by the binder, promote the granulation process, and further agglomerate to form micronuclei in combination with the effect of centrifugal force. In this process, according to the growth of the micronuclei of the phosphorus tailings, add the remaining phosphorus tailings and composite binder to the disk in small quantities and multiple times and spray water to promote the continuous growth of the micronuclei until there is no dry powder. The granulator is rotated continuously for another 4 to 5 minutes to make the particles grow to a suitable size and have a smooth and round surface, and then sieved with a 2 mm and 4.75 mm square hole sieve to obtain phosphorus tailing particles;
[0050] Step 4: After the prepared phosphate tailings particle product is passed through a 2-4 mm sieve, it is placed in an oven at 60° C. for 4 hours, then taken out and cooled at room temperature to finally obtain the phosphate tailings particle product.
[0051] Example 2
[0052] This embodiment provides a method for granulating phosphate tailings with a mussel-like structure, comprising the following steps:
[0053] Step 1, drying the phosphate tailings in an oven at 60° C. for 3 h, then crushing and passing through an 80-mesh sieve to obtain phosphate tailings powder;
[0054] Step 2, 2.5 g of tannic acid powder, 60 g of sodium lignin sulfonate powder, and 40 g of tea saponin powder were passed through an 80-mesh sieve and mixed evenly to obtain a composite adhesive;
[0055] Step 3, first put 50wt% of phosphorus tailings powder into the granulation disk, weigh the composite binder powder according to 2% of the total phosphorus tailings powder mass, evenly sprinkle 50wt% of the composite binder on the raw material mixture, and continuously clean the raw materials bonded on the disk wall with a brush to gather them in one place. At the same time, spray water in small quantities and multiple times in the disk to wet the surface of the composite raw materials and provide dissolution and reaction conditions for the binder. When the powder absorbs moisture exceeding the maximum molecular combined moisture under the action of the binder, capillary water will be formed, which can migrate faster and pull the particles around the water droplets to the center of the water droplets, combine the high viscosity provided by the binder, promote the granulation process, and further agglomerate to form micronuclei in combination with the effect of centrifugal force. In this process, according to the growth of the micronuclei of the phosphorus tailings, add the remaining phosphorus tailings and composite binder to the disk in small quantities and multiple times and spray water to promote the continuous growth of the micronuclei until there is no dry powder. The granulator is rotated continuously for another 4 to 5 minutes to make the particles grow to a suitable size and have a smooth and round surface, and then sieved with a 2 mm and 4.75 mm square hole sieve to obtain phosphorus tailing particles;
[0056] Step 4: After the prepared phosphate tailings particle product is passed through a 2-4 mm sieve, it is placed in an oven at 60° C. for 4 hours for drying, and then taken out and cooled at room temperature to finally obtain the phosphate tailings particle product.
[0057] Example 3
[0058] This embodiment provides a method for granulating phosphate tailings with a mussel-like structure, comprising the following steps:
[0059] Step 1, drying the phosphate tailings in an oven at 60° C. for 3 h, then crushing and passing through an 80-mesh sieve to obtain phosphate tailings powder;
[0060] Step 2, 2.5 g of tannic acid powder, 50 g of sodium lignin sulfonate powder, and 50 g of tea saponin powder are passed through an 80-mesh sieve and mixed evenly to obtain a composite adhesive;
[0061] Step 3, first put 50wt% of phosphorus tailings powder into the granulation disk, weigh the composite binder powder according to 2% of the total phosphorus tailings powder mass, and when the granulation disk rotates, 50wt% of the composite binder is evenly sprinkled on the raw material mixture, and the raw materials bonded on the disc wall are continuously cleaned with a brush to gather them in one place. At the same time, a small amount of water is sprayed into the disc many times to wet the surface of the composite raw materials and provide dissolution and reaction conditions for the binder. When the powder absorbs water under the action of the binder and exceeds the maximum molecular combined water, capillary water is formed, which can migrate faster and pull the particles around the water droplets to the center of the water droplets, and the high viscosity provided by the binder is combined to promote the granulation process, and further agglomerate to form micronuclei in combination with the effect of centrifugal force. In this process, according to the growth of the micronuclei of the phosphorus tailings, the remaining phosphorus tailings and composite binder are added to the disc in a small amount and many times and water is sprayed to promote the continuous growth of the micronuclei until there is no dry powder. The granulator is rotated continuously for another 4 to 5 minutes to make the particles grow to a suitable size and have a smooth and round surface, and then sieved with a 2 mm and 4.75 mm square hole sieve to obtain phosphorus tailing particles;
[0062] Step 4: After the prepared phosphate tailings particle product is passed through a 2-4 mm sieve, it is placed in an oven at 60° C. for 4 hours for drying, and then taken out and cooled at room temperature to finally obtain the phosphate tailings particle product.
[0063] Example 4
[0064] This embodiment provides a method for granulating phosphate tailings with a mussel-like structure, comprising the following steps:
[0065] Step 1, drying the phosphate tailings in an oven at 60° C. for 3 h, then crushing and passing through an 80-mesh sieve to obtain phosphate tailings powder;
[0066] Step 2, 2.5 g of tannic acid powder, 40 g of sodium lignin sulfonate powder, and 60 g of tea saponin powder were passed through an 80-mesh sieve and mixed evenly to obtain a composite adhesive;
[0067] Step 3, first put 50wt% of phosphorus tailings powder into the granulation disk, weigh the composite binder powder according to 2% of the total phosphorus tailings powder mass, and when the granulation disk rotates, 50wt% of the composite binder is evenly sprinkled on the raw material mixture, and the raw materials bonded on the disc wall are continuously cleaned with a brush to gather them in one place. At the same time, a small amount of water is sprayed into the disc many times to wet the surface of the composite raw materials and provide dissolution and reaction conditions for the binder. When the powder absorbs water under the action of the binder and exceeds the maximum molecular combined water, capillary water is formed, which can migrate faster and pull the particles around the water droplets to the center of the water droplets, and the high viscosity provided by the binder is combined to promote the granulation process, and further agglomerate to form micronuclei in combination with the effect of centrifugal force. In this process, according to the growth of the micronuclei of the phosphorus tailings, the remaining phosphorus tailings and composite binder are added to the disc in a small amount and many times and water is sprayed to promote the continuous growth of the micronuclei until there is no dry powder. The granulator is rotated continuously for another 4 to 5 minutes to make the particles grow to a suitable size and have a smooth and round surface, and then sieved with a 2 mm and 4.75 mm square hole sieve to obtain phosphorus tailing particles;
[0068] Step 4: After the prepared phosphate tailings particle product is passed through a 2-4 mm sieve, it is placed in an oven at 60° C. for 4 hours for drying, and then taken out and cooled at room temperature to finally obtain the phosphate tailings particle product.
[0069] Example 5
[0070] This embodiment provides a method for granulating phosphate tailings with a mussel-like structure, comprising the following steps:
[0071] Step 1, drying the phosphate tailings in an oven at 60° C. for 3 h, then crushing and passing through an 80-mesh sieve to obtain phosphate tailings powder;
[0072] Step 2, 2.5 g of tannic acid powder, 30 g of sodium lignin sulfonate powder, and 70 g of tea saponin powder are passed through an 80-mesh sieve and mixed evenly to obtain a composite adhesive;
[0073] Step 3, first 50wt% of the phosphorus tailings powder is put into the granulation disk, and the composite binder powder is weighed according to 2% of the total phosphorus tailings powder mass. When the granulation disk rotates, 50wt% of the composite binder is evenly sprinkled on the raw material mixture, and the raw materials bonded on the disc wall are continuously cleaned with a brush to gather them in one place. At the same time, a small amount of water is sprayed into the disc many times to make the surface of the composite raw material wet, and dissolution and reaction conditions are provided for the binder. When the powder absorbs water under the action of the binder and exceeds the maximum molecular binding water, capillary water is formed, which can migrate faster and pull the particles around the water droplets to the center of the water droplets, and the high viscosity provided by the binder is combined to promote the granulation process, and further agglomerate to form micronuclei in combination with the effect of centrifugal force. In this process, according to the growth of the micronuclei of the phosphorus tailings, the remaining phosphorus tailings and composite binder are added to the disc in a small amount and many times and water is sprayed to promote the continuous growth of the micronuclei until there is no dry powder. The granulator is rotated continuously for another 4 to 5 minutes to make the particles grow to a suitable size and have a smooth and round surface, and then sieved with a 2 mm and 4.75 mm square hole sieve to obtain phosphorus tailing particles;
[0074] Step 4: After the prepared phosphate tailings particle product is passed through a 2-4 mm sieve, it is placed in an oven at 60° C. for 4 hours for drying, and then taken out and cooled at room temperature to finally obtain the phosphate tailings particle product.
[0075] Example 6
[0076] This embodiment provides a method for granulating phosphate tailings with a mussel-like structure, comprising the following steps:
[0077] Step 1, drying the phosphate tailings in an oven at 60° C. for 3 h, then crushing and passing through an 80-mesh sieve to obtain phosphate tailings powder;
[0078] Step 2, 2.5 g of tannic acid powder, 50 g of calcium lignin sulfonate powder, and 50 g of tea saponin powder are passed through an 80-mesh sieve and mixed evenly to obtain a composite adhesive;
[0079] Step 3, first put 50wt% of phosphorus tailings powder into the granulation disk, weigh the composite binder powder according to 2% of the total phosphorus tailings powder mass, and when the granulation disk rotates, 50wt% of the composite binder is evenly sprinkled on the raw material mixture, and the raw materials bonded on the disc wall are continuously cleaned with a brush to gather them in one place. At the same time, a small amount of water is sprayed into the disc many times to wet the surface of the composite raw materials and provide dissolution and reaction conditions for the binder. When the powder absorbs water under the action of the binder and exceeds the maximum molecular combined water, capillary water is formed, which can migrate faster and pull the particles around the water droplets to the center of the water droplets, and the high viscosity provided by the binder is combined to promote the granulation process, and further agglomerate to form micronuclei in combination with the effect of centrifugal force. In this process, according to the growth of the micronuclei of the phosphorus tailings, the remaining phosphorus tailings and composite binder are added to the disc in a small amount and many times and water is sprayed to promote the continuous growth of the micronuclei until there is no dry powder. The granulator is rotated continuously for another 4 to 5 minutes to make the particles grow to a suitable size and have a smooth and round surface, and then sieved with a 2 mm and 4.75 mm square hole sieve to obtain phosphorus tailing particles;
[0080] Step 4: After the prepared phosphate tailings particle product is passed through a 2-4 mm sieve, it is placed in an oven at 60° C. for 4 hours for drying, and then taken out and cooled at room temperature to finally obtain the phosphate tailings particle product.
[0081] Example 7
[0082] This embodiment provides a method for granulating phosphate tailings with a mussel-like structure, comprising the following steps:
[0083] Step 1, drying the phosphate tailings in an oven at 60° C. for 3 h, then crushing and passing through a 40-mesh sieve to obtain phosphate tailings powder;
[0084] Step 2, 2.8 g of tannic acid powder, 70 g of sodium lignin sulfonate powder, and 30 g of tea saponin powder were passed through an 80-mesh sieve and mixed evenly to obtain a composite binder;
[0085] Step 3, first put 50wt% of phosphorus tailings powder into the granulation disk, weigh the composite binder powder according to 1.5% of the total phosphorus tailings powder mass, evenly sprinkle 50wt% of the composite binder on the raw material mixture, and continuously clean the raw materials bonded on the disc wall with a brush to gather them in one place. At the same time, spray water in small amounts and multiple times in the disc to wet the surface of the composite raw materials and provide dissolution and reaction conditions for the binder. When the powder absorbs moisture exceeding the maximum molecular combined moisture under the action of the binder, capillary water will be formed, which can migrate faster and pull the particles around the water droplets to the center of the water droplets, combine the high viscosity provided by the binder, promote the granulation process, and further agglomerate to form micronuclei in combination with the effect of centrifugal force. In this process, according to the growth of the micronuclei of the phosphorus tailings, add the remaining phosphorus tailings and composite binder to the disc in small amounts and multiple times and spray water to promote the continuous growth of the micronuclei until there is no dry powder. The granulator is rotated continuously for another 4 to 5 minutes to make the particles grow to a suitable size and have a smooth and round surface, and then sieved with a 2 mm and 4.75 mm square hole sieve to obtain phosphorus tailing particles;
[0086] Step 4: After the prepared phosphate tailings particle product is passed through a 2-4 mm sieve, it is placed in an oven and dried at 80° C. for 6 hours, then taken out and cooled at room temperature to finally obtain the phosphate tailings particle product.
[0087] Example 8
[0088] This embodiment provides a method for granulating phosphate tailings with a mussel-like structure, comprising the following steps:
[0089] Step 1, drying the phosphate tailings in an oven at 60° C. for 3 h, then crushing and passing through a 60-mesh sieve to obtain phosphate tailings powder;
[0090] Step 2, 3.0 g of tannic acid powder, 70 g of sodium lignin sulfonate powder, and 30 g of tea saponin powder were passed through an 80-mesh sieve and mixed evenly to obtain a composite binder;
[0091] Step 3, first put 50wt% of the phosphorus tailings powder into the granulation disk, weigh the composite binder powder according to 1% of the total phosphorus tailings powder mass, evenly sprinkle 50% of the binder on the raw material mixture, and continuously clean the raw materials bonded on the disc wall with a brush to gather them in one place. At the same time, spray water in small quantities and multiple times in the disc to wet the surface of the composite raw materials and provide dissolution and reaction conditions for the binder. When the powder absorbs moisture exceeding the maximum molecular combined moisture under the action of the binder, capillary water will be formed, which can migrate faster and pull the particles around the water droplets to the center of the water droplets, combine the high viscosity provided by the binder, promote the granulation process, and further agglomerate to form micronuclei in combination with the effect of centrifugal force. In this process, according to the growth of the micronuclei of the phosphorus tailings, add composite raw materials and spray water in small quantities and multiple times to the disc to promote the continuous growth of the micronuclei until there is no dry powder. The granulator is rotated continuously for another 4 to 5 minutes to make the particles grow to a suitable size and have a smooth and round surface, and then sieved with a 2 mm and 4.75 mm square hole sieve to obtain phosphorus tailing particles;
[0092] Step 4: After the prepared phosphate tailings particle product is passed through a 2-4 mm sieve, it is placed in an oven at 90°C for drying for 3 hours, and then taken out and cooled at room temperature to finally obtain the phosphate tailings particle product.
[0093] Comparative Example 1
[0094] This comparative example provides a method for granulating phosphate tailings, comprising the following steps:
[0095] Step 1, drying the phosphate tailings in an oven at 60° C. for 3 h, then crushing and passing through an 80-mesh sieve to obtain phosphate tailings powder;
[0096] Step 2, first put 50% of the phosphate tailings powder into the granulation disk, and spray water into the disk in small amounts and multiple times while the granulation disk is rotating to make the surface of the raw material wet. In this process, according to the growth of the phosphate tailings micronuclei, add the remaining phosphate tailings powder to the disk in small amounts and multiple times and spray water to promote the continuous growth of the micronuclei until there is no dry powder. The granulator continues to rotate for another 4 to 5 minutes to allow the particles to grow to a suitable size with a smooth and round surface, and then sieve with 2 mm and 4.75 mm square hole sieves to obtain phosphate tailings particles;
[0097] Step 3: After the prepared phosphate tailings particle product is passed through a 2-4 mm sieve, it is placed in an oven at 60° C. for 4 hours for drying, and then taken out and cooled at room temperature to finally obtain the phosphate tailings particle product.
[0098] Comparative Example 2
[0099] This comparative example provides a method for granulating phosphate tailings, comprising the following steps:
[0100] Step 1, drying the phosphate tailings in an oven at 60° C. for 3 h, then crushing and passing through an 80-mesh sieve to obtain phosphate tailings powder;
[0101] Step 2, using sodium lignin sulfonate as a binder;
[0102] Step 3, first put 50wt% of phosphorus tailings powder into the granulation disk, weigh the composite binder powder according to 2% of the total phosphorus tailings powder mass, evenly sprinkle 50wt% of the composite binder on the raw material mixture, and continuously clean the raw materials bonded on the disk wall with a brush to gather them in one place. At the same time, spray water in small quantities and multiple times in the disk to wet the surface of the composite raw materials and provide dissolution and reaction conditions for the binder. When the powder absorbs moisture exceeding the maximum molecular combined moisture under the action of the binder, capillary water will be formed, which can migrate faster and pull the particles around the water droplets to the center of the water droplets, combine the high viscosity provided by the binder, promote the granulation process, and further agglomerate to form micronuclei in combination with the effect of centrifugal force. In this process, according to the growth of the micronuclei of the phosphorus tailings, add the remaining phosphorus tailings and composite binder to the disk in small quantities and multiple times and spray water to promote the continuous growth of the micronuclei until there is no dry powder. The granulator is rotated continuously for another 4 to 5 minutes to make the particles grow to a suitable size and have a smooth and round surface, and then sieved with a 2 mm and 4.75 mm square hole sieve to obtain phosphorus tailing particles;
[0103] Step 4: After the prepared phosphate tailings particle product is passed through a 2-4 mm sieve, it is placed in an oven at 60° C. for 4 hours for drying, and then taken out and cooled at room temperature to finally obtain the phosphate tailings particle product.
[0104] Comparative Example 3
[0105] This comparative example provides a method for granulating phosphate tailings, comprising the following steps:
[0106] Step 1, drying the phosphate tailings in an oven at 60° C. for 3 h, then crushing and passing through an 80-mesh sieve to obtain phosphate tailings powder;
[0107] Step 2, using tea saponin as a binder;
[0108] Step 3, first put 50wt% of phosphorus tailings powder into the granulation disk, weigh the composite binder powder according to 2% of the total phosphorus tailings powder mass, evenly sprinkle 50wt% of the composite binder on the raw material mixture, and continuously clean the raw materials bonded on the disk wall with a brush to gather them in one place. At the same time, spray water in small quantities and multiple times in the disk to wet the surface of the composite raw materials and provide dissolution and reaction conditions for the binder. When the powder absorbs moisture exceeding the maximum molecular combined moisture under the action of the binder, capillary water will be formed, which can migrate faster and pull the particles around the water droplets to the center of the water droplets, combine the high viscosity provided by the binder, promote the granulation process, and further agglomerate to form micronuclei in combination with the effect of centrifugal force. In this process, according to the growth of the micronuclei of the phosphorus tailings, add the remaining phosphorus tailings and composite binder to the disk in small quantities and multiple times and spray water to promote the continuous growth of the micronuclei until there is no dry powder. The granulator is rotated continuously for another 4 to 5 minutes to make the particles grow to a suitable size and have a smooth and round surface, and then sieved with a 2 mm and 4.75 mm square hole sieve to obtain phosphorus tailing particles;
[0109] Step 4: After the prepared phosphate tailings particle product is passed through a 2-4 mm sieve, it is placed in an oven at 60° C. for 4 hours for drying, and then taken out and cooled at room temperature to finally obtain the phosphate tailings particle product.
[0110] Comparative Example 4
[0111] This comparative example provides a method for granulating phosphate tailings, comprising the following steps:
[0112] Step 1, drying the phosphate tailings in an oven at 60° C. for 3 h, then crushing and passing through an 80-mesh sieve to obtain phosphate tailings powder;
[0113] Step 2, 50g of sodium lignin sulfonate powder and 50g of tea saponin powder are passed through an 80-mesh sieve and mixed evenly to obtain a composite adhesive;
[0114] Step 3, first put 50wt% of phosphorus tailings powder into the granulation disk, weigh the composite binder powder according to 2% of the total phosphorus tailings powder mass, evenly sprinkle 50wt% of the composite binder on the raw material mixture, and continuously clean the raw materials bonded on the disk wall with a brush to gather them in one place. At the same time, spray water in small quantities and multiple times in the disk to wet the surface of the composite raw materials and provide dissolution and reaction conditions for the binder. When the powder absorbs moisture exceeding the maximum molecular combined moisture under the action of the binder, capillary water will be formed, which can migrate faster and pull the particles around the water droplets to the center of the water droplets, combine the high viscosity provided by the binder, promote the granulation process, and further agglomerate to form micronuclei in combination with the effect of centrifugal force. In this process, according to the growth of the micronuclei of the phosphorus tailings, add the remaining phosphorus tailings and composite binder to the disk in small quantities and multiple times and spray water to promote the continuous growth of the micronuclei until there is no dry powder. The granulator is rotated continuously for another 4 to 5 minutes to make the particles grow to a suitable size and have a smooth and round surface, and then sieved with a 2 mm and 4.75 mm square hole sieve to obtain phosphorus tailing particles;
[0115] Step 4: After the prepared phosphate tailings particle product is passed through a 2-4 mm sieve, it is placed in an oven at 60° C. for 4 hours for drying, and then taken out and cooled at room temperature to finally obtain the phosphate tailings particle product.
[0116] Comparative Example 5
[0117] This comparative example provides a method for granulating phosphate tailings, comprising the following steps:
[0118] Step 1, drying the phosphate tailings in an oven at 60° C. for 3 h, then crushing and passing through an 80-mesh sieve to obtain phosphate tailings powder;
[0119] Step 2, 2.5 g of tannic acid powder, 5 g of calcium lignin sulfonate powder, and 5 g of tea saponin powder were sieved through an 80-mesh sieve and mixed evenly to obtain a composite binder;
[0120] Step 3, first put 50wt% of phosphorus tailings powder into the granulation disk, weigh the composite binder powder according to 1% of the total phosphorus tailings powder mass, evenly sprinkle 50wt% of the composite binder on the raw material mixture, and continuously clean the raw materials bonded on the disk wall with a brush to gather them in one place. At the same time, spray water in small amounts and multiple times in the disk to wet the surface of the composite raw materials and provide dissolution and reaction conditions for the binder. When the powder absorbs moisture exceeding the maximum molecular combined moisture under the action of the binder, capillary water will be formed, which can migrate faster and pull the particles around the water droplets to the center of the water droplets, combine the high viscosity provided by the binder, promote the granulation process, and further agglomerate to form micronuclei in combination with the effect of centrifugal force. In this process, according to the growth of the micronuclei of the phosphorus tailings, add the remaining phosphorus tailings and composite binder to the disk in small amounts and multiple times and spray water to promote the continuous growth of the micronuclei until there is no dry powder. The granulator is rotated continuously for another 4 to 5 minutes to make the particles grow to a suitable size and have a smooth and round surface, and then sieved with a 2 mm and 4.75 mm square hole sieve to obtain phosphorus tailing particles;
[0121] Step 4: After the prepared phosphate tailings particle product is passed through a 2-4 mm sieve, it is placed in an oven at 60° C. for 4 hours for drying, and then taken out and cooled at room temperature to finally obtain the phosphate tailings particle product.
[0122] Comparative Example 6
[0123] This comparative example provides a method for granulating phosphate tailings, comprising the following steps:
[0124] Step 1, drying the phosphate tailings in an oven at 60° C. for 3 h, then crushing and passing through an 80-mesh sieve to obtain phosphate tailings powder;
[0125] Step 2, 2.5 g of tannic acid powder, 50 g of starch powder, and 50 g of tea saponin powder are passed through an 80-mesh sieve and mixed evenly to obtain a composite adhesive;
[0126] Step 3, first put 50wt% of phosphorus tailings powder into the granulation disk, weigh the composite binder powder according to 2% of the total phosphorus tailings powder mass, evenly sprinkle 50wt% of the composite binder on the raw material mixture, and continuously clean the raw materials bonded on the disk wall with a brush to gather them in one place. At the same time, spray water in small quantities and multiple times in the disk to wet the surface of the composite raw materials and provide dissolution and reaction conditions for the binder. When the powder absorbs moisture exceeding the maximum molecular combined moisture under the action of the binder, capillary water will be formed, which can migrate faster and pull the particles around the water droplets to the center of the water droplets, combine the high viscosity provided by the binder, promote the granulation process, and further agglomerate to form micronuclei in combination with the effect of centrifugal force. In this process, according to the growth of the micronuclei of the phosphorus tailings, add the remaining phosphorus tailings and composite binder to the disk in small quantities and multiple times and spray water to promote the continuous growth of the micronuclei until there is no dry powder. The granulator is rotated continuously for another 4 to 5 minutes to make the particles grow to a suitable size and have a smooth and round surface, and then sieved with a 2 mm and 4.75 mm square hole sieve to obtain phosphorus tailing particles;
[0127] Step 4: After the prepared phosphate tailings particle product is passed through a 2-4 mm sieve, it is placed in an oven at 60° C. for 4 hours for drying, and then taken out and cooled at room temperature to finally obtain the phosphate tailings particle product.
[0128] Granular product performance evaluation method:
[0129] Granulation rate: Use a 2mm to 4mm square hole sieve for screening. Particles with a particle size between 2mm and 4mm are qualified products. The granulation rate is calculated according to formula (1).
[0130] Granulation rate = m 1 / m 2 *100% (1)
[0131] In the formula, m 1 The mass of the phosphate tailings particles with a particle size between 2 mm and 4 mm; m 2 It is the total mass of powder materials mixed before granulation.
[0132] Particle strength: Take 30 fertilizer particles of uniform size and measure them using a KQ-3 particle strength meter.
[0133] Dissolution rate: Take a certain amount of phosphorus tailings particle product, the mass is recorded as m 1 , soak in still water at room temperature for 10 minutes, weigh the mass of the sample that does not pass the 1.00 mm test sieve, and record the mass as m 2 , the dissolution rate is calculated according to formula (2).
[0134] Dissolution rate = (m 1 -m 2 ) / m 1*100% (2)
[0135] The final test results are shown in Table 1.
[0136] Table 1 Properties of phosphate tailings particles
[0137] Granulation rate (%) Particle strength (N) Dissolution rate (%) Example 1 94.3 16.4 94.1 Example 2 95.4 19.7 94.5 Example 3 95.0 24.3 93.9 Example 4 94.1 25.7 92.1 Example 5 93.9 26.4 90.4 Example 6 93.8 13.4 92.4 Comparative Example 1 / / / Comparative Example 2 86.4 9.7 91.0 Comparative Example 3 87.1 19.4 83.1 Comparative Example 4 89.7 23.3 92.4 Comparative Example 5 86.4 14.5 91.4 Comparative Example 7 92.7 6.8 93.1
[0138] It should be noted that since the phosphate tailings cannot be granulated without adding a binder, the product is a fine powder, so there is no data for Comparative Example 1.
[0139] It can be seen from Table 1 that in Examples 1 to 5, as the tea saponin content increases, the particle strength tends to increase, but the dissolution rate decreases. This is mainly because after adding tea saponin, it effectively weakens the molecular attraction between the lignin-tannic acid binder, which increases the plasticity, thereby increasing the bonding force, and ultimately improving the product particle strength. Because the particles are tightly connected internally, the dissolution rate tends to decrease. Similarly, as the content of sodium lignin sulfonate increases, the particle strength tends to decrease. This is because the viscosity decreases due to the decrease in tea saponin content, and because sodium lignin sulfonate has good dispersibility, it enhances the dissolution rate of the particle product in water. Therefore, considering the comprehensive raw material cost and the actual effect of the above table, Example 3, i.e., 2.5g tannic acid powder, 5g sodium lignin sulfonate powder, and 5g tea saponin powder prepared composite binder has the best comprehensive effect at an addition amount of 2% of the mass of phosphate tailings.
[0140] In Comparative Example 1, since no binder is added, the phosphorus tailings cannot be granulated; in Comparative Example 2, sodium lignin sulfonate is used as a binder, but due to its low viscosity, the final particle strength is low and cannot meet the requirements; in Comparative Example 3, tea saponin is used as a binder, although the standard particle strength is achieved, due to its lack of swelling, the final product has low solubility and is difficult to disintegrate quickly; in Comparative Example 4, sodium lignin sulfonate and tea saponin are used as binders, and both particle strength and solubility meet the standards, but there is still a problem of low granulation rate. In Comparative Example 5, tannic acid, sodium lignin sulfonate and tea saponin are used as binders, and the added amount is controlled to be 1%. The overall effect is not as good as the 2% addition amount in Example 3, and the standard requirements cannot be met. Embodiment 6 is to use tannic acid, calcium lignin sulfonate and tea saponin as binders. Compared with sodium lignin sulfonate, calcium lignin sulfonate is a cross-linked network composed of calcium ions as a cross-linking agent, and its dissociation degree in aqueous solution is low. Its dispersibility is poor compared with sodium lignin sulfonate, so the final granulation effect is not as good as sodium lignin sulfonate; Comparative Example 6 is to use tannic acid, starch and tea saponin as binders. Starch, as a common binder, also has certain swelling and adhesion, but there is still a gap compared with lignin. Even if it can be complexed with tannic acid, the final granulation effect is still slightly insufficient. This further illustrates that the present invention uses tannic acid, sodium lignin sulfonate and tea saponin as binders. In the granulation process, tannic acid and sodium lignin sulfonate undergo complexation reaction, and tea saponin increases fluidity and surface activity, which is conducive to the composite binder penetrating into the inside of the phosphate tailings to play a bonding role, thereby improving the granulation rate, particle strength and solubility of the product particles.
[0141] To further demonstrate the effectiveness of the present invention, Example 3 and Comparative Example 2 were selected for SEM characterization analysis. Figure 1 As shown, it can be seen that in Example 3, the addition of tannic acid and tea saponin makes the particle surface and cross section closer, thereby optimizing its physical properties and ultimately improving the particle strength, which is consistent with the particle strength results of the phosphate tailings particles in Table 1.
[0142] The remaining embodiments of the present invention can achieve a granulation rate of more than 93%, a particle strength of more than 16N, and a dissolution rate of more than 90%, which can meet the national standard of calcium magnesium phosphate fertilizer of GB / T20412-2021.
[0143] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0144] Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for granulating phosphate tailings, characterized in that: The following steps are involved: The composite binder is obtained by uniformly mixing tannic acid, lignin sulfonate and tea saponin; the mass ratio of tannic acid, lignin sulfonate and tea saponin is 2.5-3:30-70:30-70; The composite binder is mixed evenly with the phosphate tailings powder and then granulated. Tannic acid and lignin sulfonate undergo a complex reaction, and tea saponin increases fluidity and surface activity, so that the composite binder penetrates into the interior of the phosphate tailings powder to play a bonding role, thereby preparing phosphate tailings particles. The addition amount of the composite binder is 1% to 2% of the mass of the phosphate tailings powder.
2. A method for granulating phosphate tailings according to claim 1, characterized in that: The mass ratio of tannic acid, lignin sulfonate and tea saponin is 2.5:30-70:30-70.
3. A method for granulating phosphate tailings according to claim 2, characterized in that: The mass ratio of tannic acid, lignin sulfonate and tea saponin is 2.5:50:
50.
4. A method for granulating phosphate tailings according to claim 1, characterized in that: The added amount of the composite binder is 2% of the mass of the phosphate tailings powder.
5. A method for granulating phosphate tailings according to claim 1, characterized in that: The lignin sulfonate is sodium lignin sulfonate or calcium lignin sulfonate.
6. A method for granulating phosphate tailings according to claim 1, characterized in that: The effective phosphorus content of phosphate tailings is 0.5% to 1%, the effective magnesium content is 4% to 7%, and the effective calcium content is 8% to 14%.
7. Phosphate tailings particles obtained by the granulation method according to any one of claims 1 to 6.
8. Use of the phosphate tailing particles according to claim 7 in soil improvement.
Citation Information
Patent Citations
Granular medium-trace nutrient element fertilizer and production method thereof
CN108503464A
A method for preparing a binder suitable for low-concentration compound fertilizers
CN109796278B
Cited By
Medium-trace granular fertilizer prepared from phosphate tailings and preparation method of medium-trace granular fertilizer
CN120398600A